Kynurenine elevation correlates with T regulatory cells increase in acute Plasmodium vivax infection: A pilot study. (14th January 2020) - dos Santos, Rafaella Oliveira; Gonçalves‐Lopes, Raquel M.; Lima, Nathália F.; Scopel, Kézia K. G.; Ferreira, Marcelo U.; Lalwani, Pritesh
Abstract: Background: Disease‐tolerance mechanisms limit infection severity by preventing tissue damage; however, the underlying mechanisms in human malaria are still unclear. Tryptophan (TRP), an essential amino acid, is catabolized into tolerogenic metabolites, kynurenines (KYN), by indoleamine 2, 3‐dioxygenase 1 (IDO1), which can induce Foxp3+ T regulatory cells (Tregs). In this study, we evaluated the relationship of these metabolites with Treg‐mediated tolerance induction in acute malaria infections. Methods: We performed a cross‐sectional study that evaluated asymptomatic, symptomatic malaria patients and endemic control patient groups. We assessed plasmatic concentration of cytokines by ELISA. Plasmatic TRP and KYN levels were measured by HPLC. Peripheral T regulatory cells were measured and phenotyped by flow cytometry. Results: The KYN/TRP ratio was significantly elevated in asymptomatic and symptomatic Plasmodium infection, compared to healthy controls. Also, Th1 and Th2 cytokines were elevated in the acute phase of malaria disease. IFN‐γ increase in acute phase was positively correlated with the KYN/TRP ratio and KYN elevation was positively correlated with the increase of peripheral FoxP3+ T regulatory cells. Conclusions: Additional studies are needed not only to identify innate mechanisms that increase tryptophan catabolism but also the role of Tregs in controlling malaria‐induced pathology and malaria tolerance by the host.